The experience of anesthesia during kidney transplantation with robot assisted laparoscopic surgery - Tekdöş Şeker, Yasemin; Saygı Emir, Nalan; Hergünsel, Oya; Tülübaş, Evrim; Öztürk, Figen; Mandacı, Derya (The European Research Journal, 2018)
Objective: Renal transplantation is the most commonly used method to improve the quality of life of patients with end-stage renal failure. Kidney transplantation began in our hospital in 2016 with robot-assisted laparoscopic surgery (RALS). Here, we retrospectively compared the RALS technique and open surgery with respect to anesthesia management during kidney transplant operations done in our clinic.Methods: Anesthesia management, the duration of the operation and of vascular anastomosis, the amount of fluid delivered perioperatively, amount of urine, and diuretic requirements were investigated retrospectively in cases of renal transplantation (Group O, open surgical technique, n = 22; Group R, RALS technique, n = 14). Blood gas values, and lactate, bicarbonate, glucose, and electrolyte levels, were examined preoperatively after extubation. Results: The durations of surgery and vascular anastomosis were significantly longer in Group R than in Group O (p < 0.05). Perioperative liquid volume was not significantly different between Groups R and A. Postoperative systolic arterial pressure was significantly higher in Group R than in Group O. As venous blood samples were obtained in Group O and arterial blood samples were obtained in Group R, blood gas parameters were evaluated within, but not between, groups. The pH and HCO3 values at the end of the operation were significantly lower, while the lactate level was significantly higher, in Group O compared to Group R (p < 0.001). There was a significant decrease in calcium level at the end of the operation versus pre-anesthesia induction in Group O, but no significant increase in the glucose level was found. There were no significant differences in sodium or potassium levels within or between the groups (p > 0.05).Conclusions: The surgical superiority of RALS technique is known. However, anesthesia management in this patient group is difficult due to the risk of the Trendelenburg position and pneumoperitoneum.